2018
DOI: 10.1108/lodj-01-2018-0053
|View full text |Cite
|
Sign up to set email alerts
|

Servant leadership and transformational leadership: from comparisons to farewells

Abstract: Purpose The purpose of this paper is to question the usefulness of comparisons between theories on servant leadership and transformational leadership. Design/methodology/approach A review of scholarly works on these two theories is presented from the original works of Greenleaf, Burns and Bass to the current research. Findings Based on the four categories of construct clarity, two competing alternatives are identifiable in the scholarship of both servant and transformational leadership. There are thus 16 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…Although most scholars understand that Greenleaf (1977) coined the term servant leadership, subsequent researchers have understood and depicted servant leaders differently with little consensus about a clear definition (Andersen, 2018; Hernandez et al , 2011; van Dierendonck, 2011). Fundamentally, however, servant leaders put followers first and help them meet their full potential (Northouse, 2018; Sendjaya et al , 2008; Spears, 2010).…”
Section: Servant Leadershipmentioning
confidence: 99%
See 3 more Smart Citations
“…Although most scholars understand that Greenleaf (1977) coined the term servant leadership, subsequent researchers have understood and depicted servant leaders differently with little consensus about a clear definition (Andersen, 2018; Hernandez et al , 2011; van Dierendonck, 2011). Fundamentally, however, servant leaders put followers first and help them meet their full potential (Northouse, 2018; Sendjaya et al , 2008; Spears, 2010).…”
Section: Servant Leadershipmentioning
confidence: 99%
“…Without clarification on the definitions of both leadership types, the comparison between transformational and servant leadership on learning organization is in vain (Andersen, 2018). Servant leadership and transformational leadership have been compared and examined in the literature with abundant organizational outcomes (Andersen, 2018; Bass, 2000; Parolini, 2007; Parolini et al , 2009; Schneider and George, 2011; Stone et al , 2004).…”
Section: Servant Leadership and Transformational Leadershipmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last two decades, scholars have extensively explored leadership based upon its various styles (Cotton, 2003), its effectiveness (Branch et al, 2013; Fullan, 2004), its various competencies (Caroll et al, 2008; Northouse, 2012), its success (Wilson, 2011) and its ability to enhance student achievement (Hallinger, 2004). Scholars who studied the effects of prominent leadership models from theoretical perspectives concluded that these theories do not apply effectively across contexts (Smothers et al, 2011 Willis et al, 2017), with one scholar predicting the imminent collapse of these theories due to their numerous variations and conceptual deficiencies (Andersen, 2018).…”
Section: Leadership Theories and Leadership Practicesmentioning
confidence: 99%